BIOPROSPECÇÃO DE FUNGOS FILAMENTOSOS ISOLADOS DE REMANESCENTES DE FLORESTA OMBRÓFILA MISTA PRODUTORES DE POLIGALACTURONASES: POTENCIAL PECTINOLÍTICO DE Penicillium sp. - WOUK, THAÍS (2017)
Pectinases have been extensively studied due to their wide variety of applications in the many industrial sectors. Among these enzymes, polygalacturonases (PG) are used mainly in the fruit juices clarification process. The selection of enzyme producing microorganisms becomes an important step in biotechnological processes. Thus, this study aimed to isolate several fungal strains and evaluate its potential production of PGs, using pineapple pell and passion fruit peel as substrates. Following the selection of the best producer strain, the Plackett-Burmann design was used in order to select the variables that most influence the production of these enzymes. Afther that, the optimal parameters for PGs production were stablishedd, using the Central Composite Rotary Design and the Response Surface Methodology. Finally, the PGs produced were biochemically characterized. As a result, 46 strains were isolated, showing, through the semi-quantitative test, the PG production hability for all strains evaluated. In the quantitative test, it was verified that the FX32 fungus was the best producer of PGs, corresponding to 6.12 U mL-1. Through the use of Plackett-Burmann design, it was found that the substrate concentration, pH and culture time were the parameters that significant influence PGs production. For these reason, these factors were considered as the independent variables in the Central Composite Rotary Design. Thus, the best conditions established for PGs production PG by Penicillium sp. were 2.9% of pineapple peel as substrate, culture pH of 7.8 and cultivation time of 8.6 days, corresponding to a production of 106.20 U mL-1. With regard to biochemical characteristics, it was verified that the enzymes produced by this fungal strain were more active at 50 °C and at pH 5.5. PGs were also very stable at pH 5.0 and 5.5, exibithing more than 80% of its initial activity under these conditions. Em relation to thermal stability, these enzymes were more stable at 45 °C. The effect of several ions and substances on the PG activity was studied. The PGs were activated by Mn2+, Ca2+ and mercaptoethanol and strong inhibited by Hg+. Finally, the hydrolysis of the pineapple peel was performed using Penicillium sp. and Aspergillus flavus crude extracts. A glucose yield equivalent to 67.42 mg g-1 substrate was achieved, under optimal hydrolysis conditions, corresponding to 15 hours of reaction, reactional pH 5.0 and reactional temperature of 50 °C. The pineapple peel was a good inducer for PGs production by Penicillium sp., as well as a promising substrate for glucose achievement through its enzymatic hydrolysis. This results provide important subsidies in order to infer industrial applications for the enzymes under study.